2022
DOI: 10.1111/1541-4337.12962
|View full text |Cite
|
Sign up to set email alerts
|

The future of functional food: Emerging technologies application on prebiotics, probiotics and postbiotics

Abstract: This review was the first to gather literature about the effect of emerging technologies on probiotic, prebiotic, and postbiotic products. Applying emerging technologies to probiotic products can increase probiotic survival and improve probiotic properties (cholesterol attachment, adhesion to Caco‐2 cells, increase angiotensin‐converting enzyme (ACE) inhibitory, antioxidant, and antimicrobial activities, and decrease systolic blood pressure). Furthermore, it can optimize the fermentation process, produce or ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 135 publications
(209 reference statements)
1
19
1
Order By: Relevance
“…As shown in Supplementary Figure S3E, following 6 h of fermentation, the pH of the fermented milk dropped to below 4.5. The rate of viable bacteria in the fermented milk was increasing, and the content of viable bacteria reached about 10 log 10 CFU, and the water-holding capacity of the fermented milk was 57.48 ± 0.01%, all of which were in accordance with the reported requirements of the marketed fermented milk (42).…”
Section: Preparation and Optimization Of Corn Fermented Milksupporting
confidence: 79%
“…As shown in Supplementary Figure S3E, following 6 h of fermentation, the pH of the fermented milk dropped to below 4.5. The rate of viable bacteria in the fermented milk was increasing, and the content of viable bacteria reached about 10 log 10 CFU, and the water-holding capacity of the fermented milk was 57.48 ± 0.01%, all of which were in accordance with the reported requirements of the marketed fermented milk (42).…”
Section: Preparation and Optimization Of Corn Fermented Milksupporting
confidence: 79%
“…As a dietary supplement, the role of probiotics is to help strengthen the host intestinal barrier, maintain gut homeostasis, and promote the immune function of the host. 44–46 Therefore, the “drug precedes bacteria” strategy is in line with mainstream clinical drug use needs. 22 The probiotic-precedes-antibiotic mode of co-administration may have two outcomes in CDI control.…”
Section: Order Of Priority In the Combination Of Bacteria And Drugmentioning
confidence: 99%
“…151 Several studies have shown that inactivated bacterial cells have prominent roles in immune regulation, anti-inflammation, anti-cancer, and the maintenance of metabolic homeostasis in the host. 45,160,163 Continuous ingestion of heat-killed L. plantarum L-137 significantly improved immune function and quality of life in healthy people, 164 and these inactivated probiotics also enhanced interferon-β levels in healthy female adults. 165 Heat-killed L. paracasei CBA L74 significantly reduced the rate of diarrhea in children.…”
Section: Upgrading Of “Bacteria–drug Combination”mentioning
confidence: 99%
“…The interest in development of foods that can positively impact human health beyond basic nutrition is gaining momentum. Although a clear definition of fortified and functional foods has been lacking, there has been a general agreement that these foods have healthy ingredients and/or nutrients (occurring naturally or produced industrially) intended to provide nutritional or health benefits (Aguilar-Pérez et al, 2021;Balthazar et al, 2022). For example, a possible procedure to prevent cardiovascular disease was suggested by Piepoli et al (2016), i.e., that consuming 2 g/day of phytosterol-rich functional foods can reduce low-density lipoprotein cholesterol by 10%.…”
Section: Food Fortification and Functional Foodsmentioning
confidence: 99%
“…Despite the benefits of functional and fortified foods, their application is challenged by certain critical limitations related to degradation and loss of functionality and the instability of bioactive compounds, affecting in particular the sensory properties of food products (Ayuso et al, 2022;Granato et al, 2020). As traditional extraction and processing methods (such as conventional thermal treatments) can cause additional challenges, emerging alternative techniques, including among others supercritical fluids, cold plasma, pulsed electric field, ultrasound, and high pressure processing have been studied (Balthazar et al, 2022), using the substantial scientific and technological advances of Industry 4.0. For example, the application of ultrasound treatment combined with pH-shifting increased the in vitro digestibility and foaming properties of amaranth protein (Figueroa-González et al, 2022).…”
Section: Food Fortification and Functional Foodsmentioning
confidence: 99%